George Matheson and Babs Vincent interviewed by Chris Sullivan in the Chris Sullivan folklore collection - Matheson, George, -1989.; Vincent, Babs, 1915-; Sullivan, Chris (Christopher Daniel), 1953- (1986)
Folkloric recording.
Recorded on 6 February 1986, at Euabalong, N.S.W.
Digital master available
Transcript available (1 p.)
Keywords: Matheson, George, -- -1989 -- Interviews; Vincent, Babs, -- 1915- -- Interviews; Aboriginal Australians -- New South Wales -- Euabalong -- Interviews; Storytellers -- New South Wales -- Euabalong -- Interviews; Folk singers -- New South Wales -- Euabalong -- Interviews; Folk songs, English -- New South Wales -- Euabalong; Folklore -- New South Wales -- Euabalong; Farm life -- New south Wales -- Euabalong -- History; Euabalong (N.S.W.) -- Social life and customs; Folk singers